ANTECEDENTS OF CUSTOMER SATISFACTION AND ITS EFFECT ON ATTITUDINAL AND BEHAVIORAL LOYALTY:: Study on Indihome Customers of PT. Telkom Indonesia Witel Bandung - Utami, Kadek Yunita; Widodo, Dr. Teguh (UTSAHA: Journal of Entrepreneurship, 2024)
As telecommunications and information technology users grow, a new innovation emerged from PT Telkom Indonesia, fixed broadband, which PT Telkom Indonesia Tbk issued its product called IndiHome in 2015. Judging from the Triple Play service which is IndiHome's flagship service, as well as other services, IndiHome's core product is its internet service. While other services such as voice (telephone) and Interactive TV (UseeTV) are augmented products. This research examines the relationship between service quality, customer satisfaction, and customer loyalty in the context of PT Telkom Indonesia's IndiHome product. IndiHome, launched in 2015, offers a core internet service with additional features like voice and interactive TV. The research aims to provide strategic recommendations to PT Telkom Indonesia to enhance customer retention as well. A quantitative, causative approach was applied, with data collected from 258 IndiHome customers in Bandung through online questionnaires. Using structural equation modeling (SEM) analysis, the research concluded that there was no statistically significant correlation between behavioral loyalty, customer satisfaction, and service quality. However, these relationships were validated when considering intervening variables.